2017
DOI: 10.3389/fnhum.2017.00566
|View full text |Cite
|
Sign up to set email alerts
|

The Dancing Brain: Structural and Functional Signatures of Expert Dance Training

Abstract: Dance – as a ritual, therapy, and leisure activity – has been known for thousands of years. Today, dance is increasingly used as therapy for cognitive and neurological disorders such as dementia and Parkinson’s disease. Surprisingly, the effects of dance training on the healthy young brain are not well understood despite the necessity of such information for planning successful clinical interventions. Therefore, this study examined actively performing, expert-level trained college students as a model of long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 101 publications
2
64
0
2
Order By: Relevance
“…This current study suggested that, compared with walking exercise, long-term TCC exercise may promote sensory-motor activation. Relatedly, Burzynska et al have investigated functional connectivity differences of 20 expert dancers within the motor learning network as compared to 20 age-and education-matched non-dancers, suggesting that expert dancers showed greater activation of the action observation network related to dance skill and balance [39]. The occipital gyrus, as an important brain region of the visual network, plays an important role in processing auditory and tactile stimuli, especially related to the accuracy of individual sound localization performance [40].…”
Section: Discussionmentioning
confidence: 99%
“…This current study suggested that, compared with walking exercise, long-term TCC exercise may promote sensory-motor activation. Relatedly, Burzynska et al have investigated functional connectivity differences of 20 expert dancers within the motor learning network as compared to 20 age-and education-matched non-dancers, suggesting that expert dancers showed greater activation of the action observation network related to dance skill and balance [39]. The occipital gyrus, as an important brain region of the visual network, plays an important role in processing auditory and tactile stimuli, especially related to the accuracy of individual sound localization performance [40].…”
Section: Discussionmentioning
confidence: 99%
“… Note: Data from these studies have previously been published elsewhere, see Study A = Hiscox et al, 2018; Hiscox, Johnson, McGarry, Marshall, et al, 2020; Hiscox, Johnson, McGarry, Schwarb, et al, 2020; Study B = Schwarb, Johnson, McGarry, & Cohen, 2016; Schwarb et al, 2019, Johnson et al, 2016; Study C = Huesmann et al, 2020; Study D = Burzynska, Finc, Taylor, Knecht, & Kramer, 2017; Study E = Schwarb et al, 2017, Johnson et al, 2018. …”
Section: Methodsmentioning
confidence: 99%
“…Based on high levels of integration of external/internal sensorimotor stimuli, dancers/musicians can make perfect performance and express emotions through sequences of tones or series of choreographic elements. Dance training is related to whole-body control, spatial integration, rhythmicity synchronization, action observation, and imitation [1] . Music training is related to the control of delicate hand or finger movements with rapid feedback of auditory, visual, and motor interaction [2].…”
Section: Introductionmentioning
confidence: 99%